Implementasi Sistem Informasi Bimbingan Konseling Pelanggaran Siswa Dengan Sistem Point - Septiano Anggun Pratama; Wirdayanti; Yuri Yudhaswana Joefrie; Wahyu Setiawan (AI Society & STMIK Indonesia, 2024)
Computer technology is currently advancing rapidly. Almost every sector of work relies on computer technology for data processing, including in the field of education, particularly in counseling services. Based on monitoring and direct interactions with teaching staff at SMK Negeri 3 Palu, it is revealed that there is currently no system available that can manage student violation incident data optimally. Instead, the process still relies on manual recording, where teachers record student violations and then submit them to the Counseling Unit (BK). Manual information management is vulnerable to the risk of data loss and information overlap. To address this situation, this research intends to develop a Web-Based Student Violation Counseling Information System with a Point System at SMK Negeri 3 Palu, focusing on improving efficiency and transparency in the point allocation process. In this study, the approach applied is the Waterfall model. With the adoption of this system, the identification of the most frequently occurring student violations becomes more detailed.